The Use of Image Cards In Developing Vocabulary Mastery For Autistic Children In Grade 1 of SLB Bintang Harapan, Bandung Regency - Permata, Adia; Khoeriah, N. Dede (Universitas Pahlawan Tuanku Tambusai, 2025)
Autism occurs due to neurological impairments that occur during early development and have a direct impact on communication patterns and social interaction, as well as affecting vocabulary deficits. The use of picture cards as a solution for children with autism spectrum disorders in pronouncing vocabulary. This study was conducted to evaluate the effectiveness of picture cards in contributing to the improvement of the ability of students with autism spectrum disorders in pronouncing new vocabulary. The method used in this study was an experiment with a Single Subject Research (SSR) approach through an A-B-A design. The research subject was a student who was the focus of the intervention. The research was conducted on one subject, namely a student with autism spectrum disorders in grade I at SDLB Bintang Harapan. The results of data analysis related to the aspect of pronouncing new vocabulary in children with autism spectrum disorders At the initial stage (baseline-1), four measurements were taken with a stable average of 43.33%, showing a small (+) increase and a level change of 6.66%. The next stage, namely intervention (B), showed consistent data after eight sessions, with a mean of 71.66%, an upward trend, and a level change of +26%. Furthermore, baseline-2 showed further improvement with an average of 74.99%, as well as an upward trend and level increase of +13.40. The conclusion of the study can be said to have been successful because the application of picture cards was able to improve the ability of children with autism spectrum disorders to pronounce new vocabulary.